Online privacy issues: Awareness, attitudes, and perceptions amongst internet users in Egypt - Alfred, Dalia Nagy Khalil (AUC Knowledge Fountain, 2014)
This study gauges the level of awareness, attitudes towards, and perceptions of online privacy policies for Internet users in Egypt. It examines how demographics as in age, gender, and education may affect the level of Internet users’awareness, attitudes, and perceptions of online privacy issues. Further, it surveys what personal information Internet users in Egypt perceive as private and accept to share with web providers, search engines or third parties. The theory of Communication Privacy Management (CPM), which was developed by Sandra Petronio, poised that Internet users choose and manage the usage of privacy policies and rules based on their cultural values, gender differences, motivations, risks and related impact. This proposition is very important for this research since it will assist in assessing the level of users’ awareness, attitudes towards, and perceptions of online privacy policies against different variables such as gender, age, and education differences.